PENGEMBANGAN ALAT EVALUASI PEMBELAJARAN KIMIA BERBASIS GAME MENGGUNAKAN APLIKASI QUIZIZZ PADA MATERI TATA NAMA SENYAWA KIMIA - Darma Gusti; Elvinawati Elvinawati; Sura Menda Ginting (ALOTROP, 2023)
This research is the creation of a Game-Based Chemistry Learning Evaluation Tool Using the Quizizz Application which aims to assist educators in evaluating the learning process and overcoming problems faced by educators and implementing the evaluation of the learning process. This evaluation tool uses a 4D development model from Thiagarajan. The study was conducted at SMAN 2 Bengkulu Selatan with a research sample of 6 chemistry teacher educators in 6 different schools and 32 students of class X MIPA 3 for the 2020/2021 academic year. The data of this study were obtained from the results of the material and media validation questionnaire, the results of the initial trial, the educator response questionnaire, and the student response questionnaire. From the research results obtained (1) the feasibility level of the evaluation tool on the material aspect is 92.61% and the media aspect is 96.43% with a very valid category. The results of the item analysis showed that 9 questions were not used and 31 questions were used, and the reliability was 0.923 in the very high category. (2) the introduction and trial phase by educators received a positive response with a percentage of 93.98%, meaning that the game-based chemistry learning evaluation tool using the quizizz application on the nomenclature of chemical compounds is very interesting and can be a solution in overcoming problems faced by educators. (3) In the trial phase, students received a positive response with a percentage of 88.84% which stated that the game-based chemistry learning evaluation tool using the quizizz application on the nomenclature of chemical compounds was very interesting.  Keywords: evaluation tool, compound nomenclature, quizizz